Evaluation of Some Nutritional Properties of Camel Meat Originating from Libya - Hamad, Ahmed; Saed Abdullah (AlQalam Journal of Medical and Applied Sciences, 2025)
The current study aims to focus on the nutritional value of camel meat. Camel meat has the same nutritional value as the main sources of red or white meat. The camel is a desert creature, its meat is just as nutritious as other red meat animals such as beef, lamb, and goat. This study indicated that the results of the approximate analysis of the components of camel meat are 18.30% protein, 2.24% fat, 1.28% ash, and 0.38% carbohydrates. The results also indicated that camel meat contains essential and non-essential amino acids. Provides requirements of children and adults. In addition, the results indicated that the fatty acid composition of camel fat includes palmitic, oleic, and linoleic acids It is a good source of the unsaturated fatty acid linoleic acid to meet nutritional needs. The percentage of unsaturated fatty acids in camel fat is 1.04%, according to available data. The results also indicated that the levels of calcium, sodium, potassium, as well as iron and copper were 6.12, 68.50, 270, 2.5, and 0.067 mg/100 gram. تهدف الدراسة الحالية إلى التركيز على القيمة الغذائية للحوم الإبل. حيث يتمتع لحم الإبل بنفس القيمة الغذائية التي تتمتع بها المصادر الأساسية للحوم الحمراء أو البيضاء. الجمل وهو مخلوق صحراوي، لحومه مغذيه تمامًا مثل الحيوانات ذات اللحوم الحمراء الأخرى كلحم البقر والضأن والماعز. ولقد أشارت هذه الدراسه ان نتائج التحليل التقريبي لمكونات لحم الإبل هي 18.30% بروتين، 2.24% دهون، 1.28% رماد، و 0.38% كربوهيدرات. كما أشارت النتائج إلى أن لحم الإبل يحتوي على أحماض أمينية أساسية وغير أساسية. يلبي احتياجات الأطفال والكبار،. بالإضافة إلى ذلك، أشارت النتائج إلى أن تركيبة الأحماض الدهنية في دهن الإبل تشمل أحماض البالمتيك، والأوليك، واللينوليك . وهو مصدر جيد للحمض الدهني اللينوليك الأساسي لتلبية الاحتياجات الغذائية . وتبلغ نسبة الأحماض الدهنية غير المشبعة في دهن الإبل 1.04% حسب النتائج. كما أشارت الدراسه إلى أن مستويات الكالسيوم والصوديوم والبوتاسيوم وكذلك الحديد والنحاس كانت 6.12 و68.50 و270 و2.5 و0.067 ملغم/100 غرام